Edvardo Turausko gyvenimo ir veiklos epizodai - Vasiliauskienė, Aldona (Lietuvos istorijos studijos, 1999)
The Lithuanian Catholic Academy of Science (LCAS), restored in Lithuania in 1990, seeks to rescue from oblivion the distinguished people of our nation - statesmen, scholars, clergymen, and public activists who were completely ignored during the Soviet period. Various jubilee celebrations serve this purpose. In 1996 scientific jubilee conferences to commemorate Edvardas Turauskas’ 30th death and 100th birth anniversaries were held in Vilnius, Endriejavas, Panevėžys, Kaunas... In this connection, numerous articles were published in periodicals, talks held over the radio, and a special booklet made up by A. Vasiliauskienė was issued by the ELTA covering the main periods of his life and activities. In this way, a lot of people learned of E. Turauskas, a striking personality of our nation. Edvardas Turauskas was director of the political department of the Lithuanian Foreign Ministry, the plenipotentiary minister of Lithuania for Czechoslovakia, Yugoslavia, and Romania, Lithuania’s delegate at the Union of Nations, the counsellor of the Embassy in Berne, Switzerland, the director of the ELTA who served the longest term in this office in inter-war Lithuania, a participant of international conferences, the editor of the daily „Rytas" and co-worker of numerous newspapers and magazines, a scholar, a person with deep Christian beliefs, an activist of the Ateitininkai movement (the first to write its history), and a member of the LCAS. He lived and worked for Lithuania; he fought for its freedom and independence... The paper reviews the most prominent periods of E. Turauskas’ life and activities and expresses a hope that it may serve as a step leading to a detailed monograph on E. Turauskas.